Influence of axial tool feed on undeformed chip geometries in power skiving gear cutting - Slipchuk, Andrii; Ondruška, Juraj; Protasov, Roman; Novitskyi, Maksym (Видавництво Львівської політехніки, 2025)
The purpose of this article was to formulate recommendations for developing strategies for multi-tool cutting of gear wheels that ensure a productive and reliable process for ensuring the accuracy and quality of machined surfaces. The determination of the effective axial feed rate to achieve maximum productivity has not yet been fully explored. The objective of this article is to ascertain and examine the impact of axial feed on the chip formation process during the cutting of the gear rim. The objective is to achieve optimal cutting conditions in each cut, thereby increasing tool life and process reliability, while concomitantly reducing processing time. The challenge of power skiving technology is to determine the effective cutting mode parameters, which include axial feed and cutting speed, depth of cut, and number of passes, as well as tool angle and cutting edge geometry of the skiving tooth. It is recommended that the optimal cutting parameters for the corresponding gear be determined based on the obtained results.
Keywords: power skiving; axial feed; undeformed chip; simulation; gear cutting process; skiver tool